Effects of lecithin and lysolecithin on the digestibility of fat sources in diets for weanling pigs - D B Jones; Jim L Nelssen; Robert H Hines; Joe D Hancock (Kansas Agricultural Experiment Station Research Reports, 1989)
Ninety-six pigs (17 d of age and 11.6 lb initial wt) were utilized to determine if adding emulsifiers (lecithin and lysolecithin) to diets containing 10% added fat would affect nutrient digestibility. Fat sources were: 1) soybean oil, 2) tallow, 3) lard, and 4) coconut oil. Lecithin and lysolecithin were added as 10% of the added fat. Pigs were limit fed using the following equation: daily feed allowance = .05 x body wt^9. After a 7-d adjustment period, feces were collected for 4 d, pooled, and analyzed for fat, nitrogen, and energy content. Soybean oil and coconut oil were more digestible than tallow and lard. Tallow was 9% more digestible when lecithin was added and 4% more digestible when lysolecithin was added. Adding the emulsifiers increased nitrogen digestibility, and lecithin increased nitrogen digestibility more than lysolecithin. Gross energy digestibilities followed the same trends as fat digestibility. Lecithin and lysolecithin have a positive effect on nutrient digestibility for weanling pigs.; Swine Day, Manhattan, KS, November 16, 1989
Keywords: Swine day; 1989; Kansas Agricultural Experiment Station contribution; no. 90-163-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 581; Swine; Lecithin; Lysolecithin; Fat source; Nutrient digestibility; Weanling pig